Characterization and fabrication of 90nm PMOS with strained silicon using TCAD silvaco / Mohd Ariff Ab Hamid - Ab Hamid, Mohd Ariff (2009)
This paper is looking into the enhancement of conventional 90nm PMOS by using graded silicon germanium layer (SiGe) within the channel and bulk of semiconductor.The performance of conventional 90nm PMOS and 90nm PMOS with silicon germanium layer was compared. A process simulation of Strained Silicon PMOS and its electrical characterization was done using TCAD tool. The analysis focused on Id-Vg, Id-Vd characteristic, and hole mobility changes. With the Germanium concentration of 35%, the threshold voltage Vt for the strained Si and conventional PMOS is -0.228035V and - 0.437378V respectively. This indicates that the strained silicon had lower power consumption. In addition, the output characteristics were also obtained for Strain Silicon PMOS which showed an improvement of drain current compared with conventional PMOS. The results were obtained from ATHENA and ATLAS simulator.